Extreme Depositional Environments: Mega End Members in Geologic Time 2003
DOI: 10.1130/0-8137-2370-1.191
|View full text |Cite
|
Sign up to set email alerts
|

Remnant-ocean submarine fans: Largest sedimentary systems on Earth

Abstract: The final stages of continental collision result in the development of remnant ocean basins, within which accumulate the most voluminous sedimentary deposits on Earth. The rapid uplift of continental crust during attempted subduction of buoyant crust results in huge sediment flux from the collision zone into nearby remnant ocean basins, where collision has yet to occur. Sediment is transported across and through foreland basins to deltas, which feed submarine fans. As diachronous suture zones migrate along str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 94 publications
(187 reference statements)
1
35
0
Order By: Relevance
“…Hundreds of millions of tons of sediment are carried each year for thousands of kilometres along the largest fluvial systems, such as the Amazon, the Ganga‐Brahmaputra or the Yellow River (Hay, ; Milliman & Farnsworth, ). Equally established is the underwater transport of large sediment volumes over similar distances via turbidity currents, such as across the present Bengal and Indus fans or their ancient analogues (Ingersoll et al ., ). Far less documented is the transport of large sediment volumes in the shallow sea, which can cover distances of a thousand kilometres and more under the action of persistent longshore currents.…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of millions of tons of sediment are carried each year for thousands of kilometres along the largest fluvial systems, such as the Amazon, the Ganga‐Brahmaputra or the Yellow River (Hay, ; Milliman & Farnsworth, ). Equally established is the underwater transport of large sediment volumes over similar distances via turbidity currents, such as across the present Bengal and Indus fans or their ancient analogues (Ingersoll et al ., ). Far less documented is the transport of large sediment volumes in the shallow sea, which can cover distances of a thousand kilometres and more under the action of persistent longshore currents.…”
Section: Introductionmentioning
confidence: 99%
“…Crustal growth is dominated by the tectonically thickened mafic lower crustal component, which was originally the depositional substrate of the turbidites. On the basis of the published (see references in the Lachlan and Rangitaton sections) and unpublished ( Figure 14 for the Damara example [92]) detrital zircon U-Pb age distributions, most of the sediment in the turbide fans is recycled from adjacent continents and arcs (see [144,145] for other examples).…”
Section: Discussionmentioning
confidence: 99%
“…As such we see no evidence for the existence of a continuous carbonate platform in this area during the Permian. Other authors have suggested that the turbidite basin is a remnant basin of the Late Paleozoic Paleo‐Tethyan Ocean between the North China and Yangtze Plates (Yin & Harrison 2000; Ingersoll et al. 2002) or an inherited foreland basin postdating the closure of the Bayan Har oceanic basin (Pan et al.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Recognition of a series of fault‐bound blocks of Permian limestone in the Triassic turbidites suggests that the turbidites were laid on a wide Permian carbonate platform that formed part of the Tethyan ocean (Yin & Zhang 1998). It has also been proposed that the Triassic turbidite basin is a remnant basin between the North China and Yangtze Plates (Yin & Harrison 2000; Ingersoll et al. 2002) or an inherited foreland basin postdating the closure of the Bayan Har oceanic basin (Pan et al.…”
Section: Introductionmentioning
confidence: 99%